2021
DOI: 10.1108/apjml-11-2019-0684
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality (AR) app use in the beauty product industry and consumer purchase intention

Abstract: PurposeDue to the lack of relevant literatures on the application of mobile augmented reality (AR) service in beauty industry, the purpose of this study is to explore the impact of the mobile AR service on consumers' purchase behavior and brand awareness in beauty industry. And this study also wants to identify the different effects of the relationship among flow experience (concentration, playfulness and exploratory behavior), decision comfort and purchase intention moderated by different levels of consumer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 90 publications
5
74
1
1
Order By: Relevance
“…Recent research also witnessed frequent switching of consumers to VR content beyond traditional realities that lends a boosting impact for responsiveness of users to product advertisements particularly in cross channel trading (Pestek and Sarvan, 2020; Liao et al , 2021). The reason is that while experiencing VR, the high sense of spatial presence it elicits brings unusual pleasure and arousal in the consumers' mind (Meißner et al , 2020; Wang et al , 2021). Thus, transformation based on the trends related to virtual reality may also help enhance customer experience with online shopping through an information delivery supported by adventurous and entertaining mobile applications.…”
Section: Research Implicationsmentioning
confidence: 99%
“…Recent research also witnessed frequent switching of consumers to VR content beyond traditional realities that lends a boosting impact for responsiveness of users to product advertisements particularly in cross channel trading (Pestek and Sarvan, 2020; Liao et al , 2021). The reason is that while experiencing VR, the high sense of spatial presence it elicits brings unusual pleasure and arousal in the consumers' mind (Meißner et al , 2020; Wang et al , 2021). Thus, transformation based on the trends related to virtual reality may also help enhance customer experience with online shopping through an information delivery supported by adventurous and entertaining mobile applications.…”
Section: Research Implicationsmentioning
confidence: 99%
“…Han et al. , 2021; Wang et al. , 2021) have investigated purchase intention as a response, they focus on the role of AR in building emotional aspects of customers' shopping experience (i.e.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…, 2017). Wang et al. (2021) recently advanced the literature by confirming the effect of customers' emotional experiences with AR on their decision comfort, but they considered only the affective aspect.…”
Section: Introductionmentioning
confidence: 99%
“…Even though decision comfort is less considered, it is a distinct construct and a critical component of a consumer's decision experience (Parker et al, 2016;Song et al, 2020). Decision comfort has been considered in various contexts, such as augmented reality (Heller et al, 2019;Song et al, 2020;Wang et al, 2021) and retail (Parker et al, 2016). These studies have shown that decision comfort has an impact on marketing-relevant concepts, such as recommendation tendency and choice commitment.…”
Section: Decision Comfortmentioning
confidence: 99%